Intervensi Dini Berbasis Keluarga Melalui Media PECS (Picture Exchange Communication System) untuk Meningkatkan Kemampuan Komunikasi Anak Autis - Zulpiani, Mardhatillah; Handayani, Endang Sri; Arnez, Gaby; Nurhastuti, Nurhastuti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Autism is a developmental and behavioral disorder characterized by difficulties in communication, which is why various intervention methods are used to address it, one of which is the Picture Exchange Communication System (PECS). This research aims to determine whether the application of the PECS method can improve communication skills in children with autism. The method used is an experimental method, as this research is conducted with the aim of observing the effects of a treatment. Based on the results of the program for children with interaction and communication impairments that we applied to the subject with the initials SHD using PECS media over 5 meetings in Phase I, the result is that SHD can perform the Phase I tasks well and correctly. The result is that SHD was able to carry out Phase I tasks well and correctly. This allows SHD to proceed to Phase II of PECS, and if successful in this phase, it can continue to the next stages up to Phase VI. The use of the PECS method should be implemented intensively to achieve more optimal results, both in school and continued at home with guidance from parents. It is recommended for those who want to implement the PECS method to read the PECS method guidebook to gain a clear understanding and perspective, thus helping children develop their communication skills.